Local Rulers in North Cameroon. The Interplay of Politics and Conversion - Schilder, Kees (Afrika Focus, 1993)
This article analyses the conversion to Islam of indigenous chiefs in North Cameroon. The chiefs studied belong to the Mundang ethnic group. Their islamisation is interpreted as the outcome of the ambivalence brought about by their intermediary role between local society and the wider society. This approach offers insights in (a) the connection between conversion and political careers; (b) the relation between Islam and ethnic identities; and (c) the popular legitimacy of conversion. KEY WORDS: Cameroon, Mundang, chiefs, Islam, ethnicity, cosmology